Contextualizing Fiqh al-Munakahat through Short Filmmaking: A Legal Constructivist Approach - Johar, Rama Dhini Permasari; Satrial, Ardi; Yulia, Sispa; Alouzi, Khuloud Mustafa (International Journal of Islamic Studies Higher Education, 2025)
This study discusses a project-based learning model in the form of a short film project designed and performed by students themselves. This study aims to analyze the extent to which this short film project is effective and interesting for students in understanding the material on fiqh munakahat. Furthermore, it is interesting to analyze how students are able to build their understanding of the material on talaq ba'in kubra through this short film project. The author uses a multidisciplinary theory, namely the theory of project-based learning in Islamic education and the theory of legal constructivism in analyzing the data. In conducting this research, the author uses a mixed method design approach with a concurrent embedded strategy model. The subjects of this study were eleven students at a boarding school in West Sumatra, Indonesia, who were involved in the short film project. The data analysis technique used by the author was thematic analysis for qualitative data, while the quantitative data analysis technique used a simple statistical test (t-test). The results of this study indicate that the learning model using the short film production project is highly effective in enhancing students' abilities in the following areas: more practical and interactive learning, increased interest and motivation to learn, easier understanding of concepts, and promotion of collaboration and teamwork. Furthermore, from a legal constructivist perspective, it demonstrates that understanding of fiqh munakahat can be developed through real-world experiences in the short film production project itself, rather than solely through lecture-based methods and rote memorization of texts. Thus, short film production is not merely a learning tool but also a constructivist strategy for fostering a deeper and more contextual understanding of Islamic law among students.